MSMEs in Developing Economies and Their Role in Achieving Sustainable Development Goals in the Context of Covid19: A Theoretical Exposition - Himachalam Dasaraju; Kishore Somalaraju; Sreenivasa Murthy Kota (International Journal of Small and Medium Enterprises and Business Sustainability, 2020)
The present paper aims to review the importance, progress and the role of micro, small, and medium enterprises (MSMEs) in achieving the Sustainable Development Goals (SDGs) in the developing economies in the wake of Covid-19. It analyzed theoretically in the context of Indian MSMEs. The vital contribution of MSMEs to broader social-economic objectives, including job creation and poverty alleviation makes them a key priority area for achieving the SDGs. It gained a lot of importance in achieving SDGs in the developed economies in general and in developing economies, in particular, owing to its inherent characteristics of inclusive growth and sustainable development. The employment generation through MSMEs will often directly benefit the poor and vulnerable, particularly women and youth, thereby directly reducing poverty, increasing economic status, and reduce the severity of hungry. Further, it leads to nurturing entrepreneurship, which is an engine of inclusive growth and stimulus for economic prosperity and empowering people. All the developing economies including India has taken several measures to promote MSMEs by starting various flagship programs and initiatives. Apart from the various governmental measures initiated globally, the MSMEs sector is not free from myriad problems and it requires more stimulus to strengthen it further. As the present global Covid-19 pandemic lockdown has disrupted badly the functioning of MSMEs, it is the dire need of the day to promote this sector and make it viable to access to the new technology, market competitiveness, and global markets, to play an active and vital role in achieving SDGs by 2030 as per UN targets